Der Abschluss des Zwölfprophetenbuches: Buchübergreifende Redaktionsprozesse in den späten Sammlungen - Wöhrle, Jakob (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2008)
This volume presents a study of the late stages in the genesis of the Book of the Twelve; it is based on a complete analysis of the editorial history of the Books of Obadiah, Jonah, Nahum, Habakkuk, Deuterozachariah und Malachi and leads to a new model for the origin of the Book of the Twelve Prophets